Variational Iteration Method for Solving Multi-Fractional Integro Differential Equations - I. Khaleel, Omar (Iraqi Journal of Science, 2023)
In this paper, we present an approximate method for solving integro-differential equations of multi-fractional order by using the variational iteration method.First, we derive the variational iteration formula related to the considered problem, then prove its convergence to the exact solution. Also we give some illustrative examples of linear and nonlinear equations.